Clinical Governance Implementation Strategies in Improving Accreditation Standard Compliance at Central Surgical Installations: A Literature Review - Putra Imanullah; Benny Hosiana Tumbelaka (LPPM Universitas Respati Indonesia, 2026)
Background: The Central Operating Theatre (COT) is a high-risk unit demanding zero-tolerance for clinical errors. Although hospital accreditation is a national mandate, field compliance often falls into the phenomenon of formalistic compliance—a condition where standards are met only administratively to fulfill periodic evaluation requirements. A paradigm shift through clinical governance is essential to transform this passive adherence into an internalized and sustainable work culture. Objective: This study aims to synthesize effective clinical governance implementation strategies to ensure consistent quality, particularly within the Anesthesia and Surgical Care (ASC) and Patient Safety Goals (PSG) standards. Methods: An integrative literature review was conducted by analyzing studies from PubMed, Google Scholar, and ScienceDirect databases spanning 2016–2026. The analysis focused on integrating clinical governance pillars with the latest health regulation dynamics in Indonesia. Results: Findings indicate that enduring compliance is only achievable through robust clinical leadership capable of fostering an ecosystem of psychological safety. In this environment, every team member is encouraged to voice concerns for patient safety without hesitation. Furthermore, the Surgical Safety Checklist (SSC) is reconstructed not merely as an administrative burden but as a primary medico-legal protection instrument for medical professionals under Indonesia’s Health Law No. 17 of 2023. The researcher formulated